Performance study of an innovative concept of hybrid constructed wetland-extensive green roof with growing media amended with recycled materials. (1st April 2023) - Petreje, Marek; Sněhota, Michal; Chorazy, Tomáš; Novotný, Michal; Rybová, Barbora; Hečková, Petra
Abstract: Implementation of green roofs requires a large amount of primary material, especially for constructing the growing media layer. In addition, irrigation of green roofs with potable water is uneconomical and unsustainable. The novel hybrid green roof system proposed in this paper is in line with the principles of circular economy as it incorporates recycled materials into green roof growing media and greywater for irrigation. Two experimental beds were built to evaluate the concept of treating greywater in a constructed wetland prior to using it to irrigate a dual-layer extensive green roof. The growing media in both two extensive green roof beds contained ca. 37.5% by volume of recycled crushed building rubble containing a large proportion of brick. One of the two beds additionally contained 9.5% by volume of sewage sludge-based biochar. The concept of the hybrid roof and novel growing media was evaluated based on laboratory analysis of the growing media and on onsite measurements of hydraulic and thermal performance. The growing media amended with recycled materials developed in this study had hydrophysical properties comparable to commercially available growing media without recycled materials. Observations made during one vegetation season from June to October and a ten day-intensive water quality monitoring campaign during September 2020 showed that the constructed wetland significantly reduced total nitrogen and orthophosphate concentrations in pre-treated greywater. Due to the irrigation method employed, in which water flowed predominantly through drainage mats below the growing media, nutrient-leaching by the irrigation water was avoided. Concentrations of nutrients in the effluent were observed to increase only in response to precipitation. The temperature peak of the bottom green roof layer was shifted by almost 9 h from the peak in air temperature, and temperature fluctuations were significantly reduced. Vegetation on the bed amended with biochar demonstrated more vigorous growth due to available nutrients in the biochar which increased the rate of temperature-reducing evapotranspiration. More water evapotranspirated more water, which provided more water retention capacity confirmed by a lower runoff coefficient. Simple storage routing hydraulic modeling of hybrid green roof runoff using a nonlinear reservoir was performed. Graphical abstract: Image 1 Highlights: Hybrid constructed wetland - green roof concept was developed. Performance of the concept was successfully tested on experimental beds. Biochar and recycled crushed brick were used in newly developed growing media. Ability of CW to reduce nutrient concentration was confirmed. Runoff was successfully simulated by non-linear reservoir model.